Occupational Therapy in Kleefstra Syndrome: A Case Report - ghaffari, shakiba; Kalantari, Minoo (Iranian Journal of Child Neurology, 2024)
Kleefstra Syndrome is a rare genetic neurodevelopmental disorder caused by a microdeletion in chromosomal region 9q34.3 or a mutation in the EHTM1 gene. Patients with KS show a range of clinical symptoms, including delay in motor and speech development, intellectual disability, autistic-like features, childhood hypotonia, and distinctive facial dysmorphic features. The patient is a 4-year-old girl who was initially diagnosed with developmental motor delay by a pediatric neurologist and referred to an occupational therapy clinic at 6 months of age. The initial assessment showed hypotonia and difficulties with rolling. Occupational therapy intervention was based on principles of neurodevelopmental treatment and sensory integration with cognitive integration and activities of daily living training. With continuous occupational therapy services over more than 3 years, she overcame many disabilities and improved in occupational performance skills such as gross and fine motor skills as well as cognitive abilities, although her verbal communication skill is not effective. The patient's progress was as follows: she began rolling over at 7 months, achieved independent sitting at 10 months, crawled at 18 months, stood with support at 20 months, and took her first steps at 26 months. The predominant problem was speech delay which was noticeable in this syndrome. When a patient is being referred because of Kleefstra syndrome, occupational therapy, and speech therapy assessments should be accurately implemented.